2022
DOI: 10.1097/inf.0000000000003797
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biologic Characteristics of Kingella kingae-Induced Septic Arthritis of the Knee in Young Children

Abstract: Background and Objectives: Septic arthritis of the knee is presumed to be the most frequent form of Kingella kingae-induced osteoarticular infection. This study aimed to report on the clinical course, biological parameters, and results of microbiological investigations among children with K. kingae-induced septic arthritis of the knee. It also assessed the modified Kocher–Caird criteria’s ability to predict K. kingae-induced septic arthritis of the knee. Methods: The medical charts of 51 children below 4 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…For example, a recent study from Geneva found that of 47 children with confirmed K . kingae septic arthritis, only 6 were positive on culture whereas 44 were positive with PCR assays 8 …”
mentioning
confidence: 99%
“…For example, a recent study from Geneva found that of 47 children with confirmed K . kingae septic arthritis, only 6 were positive on culture whereas 44 were positive with PCR assays 8 …”
mentioning
confidence: 99%